2008
DOI: 10.1074/jbc.m708177200
|View full text |Cite
|
Sign up to set email alerts
|

AMP-activated Protein Kinase Is Activated as a Consequence of Lipolysis in the Adipocyte

Abstract: AMP-activated protein kinase (AMPK) is activated in adipocytes during exercise and other states in which lipolysis is stimulated. However, the mechanism(s) responsible for this effect and its physiological relevance are unclear. To examine these questions, 3T3-L1 adipocytes were treated with cAMP-inducing agents (isoproterenol, forskolin, and isobutylmethylxanthine), which stimulate lipolysis and activate AMPK. When lipolysis was partially inhibited with the general lipase inhibitor orlistat, AMPK activation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
207
3
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(227 citation statements)
references
References 81 publications
13
207
3
1
Order By: Relevance
“…Interplay between cAMP and AMPK signaling in adipocytes may also contribute to the ␤-AR-mediated decrease in leptin release (23,31,87). Koh et al (31) showed that ␤-AR agonists increase the AMP/ATP ratio and activate AMPK activity in rat adipocytes.…”
Section: Signaling Pathways Involved In Insulin and Amino Acid-stimulmentioning
confidence: 99%
See 2 more Smart Citations
“…Interplay between cAMP and AMPK signaling in adipocytes may also contribute to the ␤-AR-mediated decrease in leptin release (23,31,87). Koh et al (31) showed that ␤-AR agonists increase the AMP/ATP ratio and activate AMPK activity in rat adipocytes.…”
Section: Signaling Pathways Involved In Insulin and Amino Acid-stimulmentioning
confidence: 99%
“…Koh et al (31) showed that ␤-AR agonists increase the AMP/ATP ratio and activate AMPK activity in rat adipocytes. A recent paper by Gauthier et al (23) showed that ␤-AR-stimulated lipolysis increases use of ATP for FA activation and that this activates AMPK activity. Thus it seems possible that the decline in serum leptin associated with activation of the sympathetic nervous system with fasting, cold, or exercise involves the cross-talk among the PKA, AMPK, and mTOR pathways, as illustrated in Fig.…”
Section: Signaling Pathways Involved In Insulin and Amino Acid-stimulmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding adipocytes responses to acute exercise, Wohlers et al demonstrated that acute exercise elevated the expression of ATGL and HSL Ser660 phosphorylation 21) . Another study demonstrated that AMP-activated protein kinase (AMPK), a sensor of cellular energy state that responds to metabolic stress and other regulatory signals, was activated during lipolysis in adipocytes due to an increase in the AMP/ATP ratio 22) . As well, Ruderman et al demonstrated that AMPK activity was increased in adipose tissue 30 min following treadmill running exercise in normal rats 23) , and the administration of AMPK activator N 1 -(β-D-Ribofuranosyl)-5-aminoimidazole-4-carboxamide (AICAR) to rats diminished adiposity 24) .…”
Section: Exercise Training and Lipolytic Activity In Adipocytesmentioning
confidence: 99%
“…It seems counter-intuitive (Daval et al 2006) that AMPK inhibits lipolysis, although it is itself activated in situations of increased lipolysis. It could be speculated (Djouder et al 2010;Sponarova et al 2005;Daval et al 2006;Gauthier et al 2008) that AMPK-induced reduction of lipolysis could be a feed back mechanism limiting the cellular energy drain, because part of the fatty acids released can be re-activated to acyl-CoA and re-esterified which requires ATP and generates AMP. Also, accumulation of large amounts of fatty acids could be deleterious for the cells.…”
Section: Ampk Function In Adipose Tissuementioning
confidence: 99%